Analisis Pelayanan Publik dalam Pengurusan Administrasi Surat Menyurat di Kantor Lurah Kenangan Baru Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Ulfa Maharani; Beby Mashito Batubara; Walid Mustafa (Universitas Medan Area, 2022)
The implementation of good governance must be carried out in every public sector because it applies the principles in regulating government that allow efficient and transparent administrative services so that the management can meet the needs of the community in obtaining services so that governance can run well. The purpose of this study was to determine the service at the Kenangan Baru Village Office, Percut Sei Tuan District, Deli Serdang Regency in providing services to the community, especially in the correspondence administration section. This research method uses qualitative techniques through interviews, observations, and documentation. The results of the study indicate that the government apparatus of Kenangan Baru Village in providing services is still not optimal in terms of procedures in service, efficiency in service, timeliness in service and competence of service officers. This is due to the lack of discipline and professionalism of Kenangan Baru Village employees in providing services to the community.